Initiatives on early detection and intervention to proactively identify health and social problems in older people: experiences from the Netherlands. Issue 1 (December 2015) - Lette, Manon; Baan, Caroline; van den Berg, Matthijs; de Bruin, Simone
Abstract Background Over the last years, several initiatives on early detection and intervention have been put in place to proactively identify health and social problems in (frail) older people. An overview of the initiatives currently available in the Netherlands is lacking, and it is unknown whether they meet the preferences and needs of older people. Therefore, the objectives of this study were threefold: 1. To identify initiatives on early detection and intervention for older people in the Netherlands and compare their characteristics; 2. To explore the experiences of professionals with these initiatives; and 3. To explore to what extent existing initiatives meet the preferences and needs of older people. Methods We performed a qualitative descriptive study in which we conducted semi-structured interviews with seventeen experts in preventive elderly care and three group interviews with volunteer elderly advisors. Data were analysed using the framework analysis method. Results We identified eight categories of initiatives based on the setting (e.g. general practitioner practice, hospital, municipality) in which they were offered. Initiatives differed in their aims and target groups. The utilization of peers to identify problems and risks, as was done by some initiatives, was seen as a strength. Difficulties were experienced with identifying the target group that would benefit from proactive delivery of care and support most, and with addressing prevalent issues among older people (e.g. psychosocial issues, self-reliance issues). Conclusion Although there is a broad array of initiatives available, there is a discrepancy between supply and demand. Current initiatives insufficiently address needs of (frail) older people. More insight is needed in "what should be done by whom, for which target group and at what moment", in order to improve current practice in preventive elderly care.